Nalar Hukum Fiqih Syafi’iyyah Dalam Penentuan Status Nasab Anak Hasil Perselingkuhan - Kurniawan, Rizki; Al Amin, Habibi (Maqasid: Jurnal Studi Hukum Islam, 2023)
Divorce is one of kind things that led to break up the marriage relationship. One of these effects is the loss of a husband obligation to support a woman who become his ex-wife. Nevertheless, the obligation to provide for the child who born from the marriage should not to be extended to his dad. This is being weakened in practice, for making of a living rights depends to a large extent on someone’s understanding and ability. This study focuses on two things, namely how the legal reasoning of Syafi'iyyah fiqh in determining the lineage of children resulting from infidelity and how the consequences that will be obtained by children resulting from infidelity related to their rights as a child. The method used in this research is literature study with deductive analysis method. The primary sources in this study are several books of ushul fiqh and books of fiqh mu'tabaroh madzhab syafi'iyyah. The results of this study indicate that in the Syafi'iyyah madzhab, the lineage of children resulting from cheating is not attributed to their biological father, this is based on legal reasoning taken from the hadith about firasy and the implications it gets are the fall of the law and rights related to the child, i.e. both do not inherit each other, the father is not obliged to provide for him, if the child is a girl, then the father is not a mahram for the child and the father cannot be his guardian.